Parbhani Vasant' (PVRSG 101): A Novel Rabi Sorghum Variety for Hurda Production Released for the Marathwada Region of Maharashtra, India - H.V. Kalpande; A.W. More; R.R. Dhutmal; K. S. Baig; S. G. Shinde; S.P. Mehtre; R. L. Aundhekar; A. B. Bagade; S. B. Pawar; D. K. Patil (The Bioscan, 2025)
Background: Sorghum (Sorghum bicolor (L.) Moench) is a vital staple crop globally, particularly in the semi arid tropics, serving as a primary source of food and fodder [1]. In India, post-rainy season (Rabi) sorghum holds significant importance, especially in the state of Maharashtra, where it is valued for its superior grain quality and drought resilience [2]. A growing niche market is the consumption of tender, sweet sorghum grains, known as Hurda, which is gaining popularity due to its nutritional profile and use in agro-tourism [3]. The current challenge is the lack of high-yielding, quality-specific, and pest-tolerant varieties tailored for dedicated Hurda production in the Marathwada region.